The Comparison of the Effects of Training Self-awareness and Problem-solving Skills on Marital Satisfaction of Married Women: A Randomized Controlled Trial - Saba Moodi; Zahra Mehrbakhsh; Fatemeh Amtaeh; Sedigheh Moghasemi (Shiraz University of Medical Sciences, 2022)
Background: One of the most important causes of marital dissatisfaction is the lack of life skills. This study aimed to compare the effects of training self-awareness and problem-solving skills on marital satisfaction of married women.Methods: This study was a randomized field trial conducted in Gorgan since October 2019 to September 2020. A total of 105 married women were allocated to one of two interventions or a control group based on triplex block randomization. Data collection tools were the Persian version of the self-awareness questionnaire, problem-solving questionnaire and Four ENRICH Couple Scales. The participants completed the questionnaires before (T1), immediately (T2), and one month after the intervention completion (T3). The first intervention group received self-awareness skills training and the second received problem-solving skills training one session per week for four weeks. The control group did not receive any training. Data were analyzed using One-way ANOVA, Kruskal-Wallis, Chi-square, Fishers exact test, exact test, repeated measure ANOVA, and Bonferroni test, using SPSS 16. A P value <0.05 was considered significant.Results: The mean score of ENRICH Scales in the three groups, immediately and one month after the intervention, were not statistically significant (P>0.05). However, in the problem-solving group, the scale of marital satisfaction was significantly different at T2 and T3 (31.40±4.55, 33±5.21, P=0.008). In the self-awareness training group at T1 and T3, the mean of the conflict resolution scale (32.60±63.28, 33.94±5.74, P=0.03) was significantly different.Conclusion: The results showed that problem-solving skills training was more effective in increasing the score of marital satisfaction compared to self-awareness skills training.Trial Registration Number: IRCT20190721044290N1.